2020
DOI: 10.1007/s00192-020-04405-2
|View full text |Cite
|
Sign up to set email alerts
|

A one-stop perineal clinic: our eleven-year experience

Abstract: Introduction and hypothesis The perineal clinic is a dedicated setting offering assessment for various childbirth-related presentations including obstetric anal sphincter injuries (OASIs), perineal wound complications, pelvic floor dysfunction and other conditions such as female genital mutilation(FGM). We describe the clinical presentation and outcomes of women from a tertiary perineal clinic based on data collected over an 11-year period. Methods This is a retrospective observational study. A one-stop outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Episiotomy is intended to prevent severe perineal tears (e.g., OASIS) that may result during transvaginal delivery ( 40 ). Some studies have reported that the incidence of OASIS ranges from 0.25 to 7.31% in women who deliver vaginally, and this delivery complication can have a significant impact on maternal health and may lead to a range of problems such as anal incontinence, urinary incontinence, wound infection, perineal pain, sexual dysfunction, and postpartum depression, and a high proportion (42%) of wound complications required further specialist treatment ( 41 45 ). This analysis showed a lower rate of tearing with small-angle lateral perineotomy and no substantial difference in the rate of third- or fourth-degree perineal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Episiotomy is intended to prevent severe perineal tears (e.g., OASIS) that may result during transvaginal delivery ( 40 ). Some studies have reported that the incidence of OASIS ranges from 0.25 to 7.31% in women who deliver vaginally, and this delivery complication can have a significant impact on maternal health and may lead to a range of problems such as anal incontinence, urinary incontinence, wound infection, perineal pain, sexual dysfunction, and postpartum depression, and a high proportion (42%) of wound complications required further specialist treatment ( 41 45 ). This analysis showed a lower rate of tearing with small-angle lateral perineotomy and no substantial difference in the rate of third- or fourth-degree perineal tears.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why the iMSP, which correlates with anal sphincter function [18], increased significantly between the time period of 30 months following OASI and the subsequent pregnancy in those women with a sphincter defect ≤ 1 h. However, another reason for functional improvement is recovery of muscle strength with pelvic and anal sphincter exercises. In our dedicated perineal service, all women who have sustained an OASI are advised to start pelvic floor muscle training (PFMT) [25]. Information is provided using patient information leaflets and mobile health applications prior to discharge [26].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, this was a prospective cohort study at Croydon University Hospital (CUH), which was conducted to assess the clinical progression of perineal wound infection and its effect on anal sphincter integrity using endoanal (EAUS) and transperineal ultrasound (TPUS). The primary aim of the PERINEAL study was to evaluate the effect of perineal wound infection on anal sphincter integrity in women with and without obstetric anal sphincter injuries (OASIs) using 3D EAUS and 4D TPUS [6]. Ethical approval was obtained from NHS Health Research Authority, London -Surrey Research Ethics Committee (20/LO/0304).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, women often have poor experiences with the clinical management of perineal wound complications due to a paucity of information about clinical management and recovery [5]. Therefore, perineal clinics have been established to improve the care of perineal trauma in the postpartum period, however there is disparity with regards to the availability of these services [6].…”
Section: Introductionmentioning
confidence: 99%